Development in-house: a trap method for pretreatment of fat, oil, and grease in kitchen wastewater - Radin Mohamed, R. M. S.; Al-Gheethi, Adel; Welfrad, A. N.; Amir Hashim, M. K. (Springer Nature, 2018)
Most of the commercial restaurant and domestic house kitchen does not equip with the proper kitchen wastewater treatment. These wastes contain high concentrations of fat, oil, and grease (FOG) which are disposed into the sewerage network and increase the sanitary sewer overflow (SSO). The present chapter discusses the individual treatment systems which are used for the removal of FOG from the kitchen wastewater. The most common and cheapest FOG treatment system is by using the gravity separation. However, in order to increase the efficiency of these systems, some of the researchers have been using natural materials to enhance the adsorption process of FOG. The establishment of a reliable FOG treatment system for each house based on the separation system might contribute effectively in the FOG removal concentration in the kitchen wastewater.